2018
DOI: 10.1155/2018/5018460
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Blood Vessels on Temperature during High-Intensity Focused Ultrasound Hyperthermia Based on the Thermal Wave Model of Bioheat Transfer

Abstract: The coupled effects of blood vessels and thermal relaxation time on temperature and thermal lesion region in biological tissue during high-intensity focused ultrasound (HIFU) hyperthermia are numerically investigated. Considering the non-Fourier behavior of heat conduction in biological tissue, the traditional Pennes bioheat equation was modified to thermal wave model of bioheat transfer (TWMBT). Consequently, a joint physical model, which combines TWMBT for tissue and energy transport equation for blood vesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Previously, clinicians were concerned that blood flow in tissues could dissipate the generated heat during HIFU treatment, causing insufficient thermal effects for tumor ablation. 20 Such a heat sink effect may spare a large number of live tumor cells after HIFU treatment, leading to recurrence later. Further increasing the power output to increase the temperature may cause skin burns and pain, making analgesic and fractionated treatment compulsory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, clinicians were concerned that blood flow in tissues could dissipate the generated heat during HIFU treatment, causing insufficient thermal effects for tumor ablation. 20 Such a heat sink effect may spare a large number of live tumor cells after HIFU treatment, leading to recurrence later. Further increasing the power output to increase the temperature may cause skin burns and pain, making analgesic and fractionated treatment compulsory.…”
Section: Discussionmentioning
confidence: 99%
“…The disadvantages of HIFU include (i) blood flow within the tissue causes a heat sink effect during HIFU, 20 which may reduce the thermal energy crucial for thorough coagulative necrosis and leave residual tumor cells that may regrow and (ii) cancer cells between coagulated foci may escape from thermal damage irrespective of the density of the HIFU matrix.…”
Section: Introductionmentioning
confidence: 99%
“…When the distance between the surface of the blood vessel and the focal point is 2.5 mm, the temperature at the focal point was saturated after approximately 50 s of radiation, and the maximum cooling caused by the blood flow was approximately 0.5 °C when the supply of radiation was ceased 90. Based on the thermal wave model of bioheat transfer, Tan et al numerically investigated the influence of blood vessels on temperature during high-intensity focused ultrasound hyperthermia 91. The results showed that a longer duration of thermal relaxation leads to the production of smaller thermal lesions.…”
Section: Ultrasonic Effects and Enhancement On Eprmentioning
confidence: 99%
“…Through a voltage-calibration method, Zhang et al investigated the feasibility of TWMBT in the radiofrequency ablation (RFA) simulation, the results suggested that the prediction of TWMBT was 0.55 °C more accurate than Pennes equation, declared that TWMBT could be used as an alternative in the simulation of long-duration high intensity RFA [13]. In recent years, TWMBT also has been employed to study bio-heat transfer during HIFU [14][15][16][17]. Liu et al [14] and Gupta et al [16] used TWMBT to estimate the temperature elevation induced by HIFU in biological tissues.…”
Section: Introductionmentioning
confidence: 99%